How do you find the derivative of #f(x) = 1/sqrt(2x-1)# by first principles?

Answer 1

derivative of function to a power #-1/2 2(2x-1)^(-1/2-1)#

#f(x) = (2x-1)# You want the derivative of f to the power #-1/2# Chain rule #-1/2 2(2x-1)^(-1/2-1)#

The factor 2 comes from the derivative of f itself

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

Use limit definition of derivative to find:

#f'(x) = -(2x-1)^(-3/2)#

#f(x) = 1/sqrt(2x-1)#
#f'(a) = lim_(h->0) (f(a+h) - f(a))/h#
#=lim_(h->0) (1/sqrt(2a+2h-1) - 1/sqrt(2a-1))/h#
#=lim_(h->0) (sqrt(2a-1)-sqrt(2a+2h-1))/(h sqrt(2a+2h-1) sqrt(2a-1))#
#=lim_(h->0) ((sqrt(2a-1)-sqrt(2a+2h-1))(sqrt(2a-1)+sqrt(2a+2h-1)))/(h sqrt(2a+2h-1) sqrt(2a-1) (sqrt(2a-1)+sqrt(2a+2h-1)))#
#=lim_(h->0) ((2a-1)-(2a+2h-1))/(h sqrt(2a+2h-1) sqrt(2a-1) (sqrt(2a-1)+sqrt(2a+2h-1)))#
#=lim_(h->0) (-2h)/(h sqrt(2a+2h-1) sqrt(2a-1) (sqrt(2a-1)+sqrt(2a+2h-1)))#
#=lim_(h->0) (-2)/(sqrt(2a+2h-1) sqrt(2a-1) (sqrt(2a-1)+sqrt(2a+2h-1)))#
#=(-2)/(sqrt(2a-1) sqrt(2a-1) (sqrt(2a-1)+sqrt(2a-1)))#
#=(-1)/((2a-1)^(3/2))#
#=-(2a-1)^(-3/2)#

So:

#f'(x) = -(2x-1)^(-3/2)#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 3

To find the derivative of ( f(x) = \frac{1}{\sqrt{2x - 1}} ) using first principles, we start with the definition of the derivative:

[ f'(x) = \lim_{h \to 0} \frac{f(x + h) - f(x)}{h} ]

First, we need to find ( f(x + h) ):

[ f(x + h) = \frac{1}{\sqrt{2(x + h) - 1}} ]

Now, substitute ( f(x + h) ) and ( f(x) ) into the difference quotient:

[ f'(x) = \lim_{h \to 0} \frac{\frac{1}{\sqrt{2(x + h) - 1}} - \frac{1}{\sqrt{2x - 1}}}{h} ]

Next, we rationalize the numerator by multiplying both the numerator and the denominator by the conjugate of the numerator:

[ f'(x) = \lim_{h \to 0} \frac{\sqrt{2x - 1} - \sqrt{2(x + h) - 1}}{h\sqrt{2(x + h) - 1}\sqrt{2x - 1}} ]

Now, combine the terms in the numerator:

[ f'(x) = \lim_{h \to 0} \frac{\sqrt{2x - 1} - \sqrt{2x + 2h - 1}}{h\sqrt{2(x + h) - 1}\sqrt{2x - 1}} ]

To simplify further, factor out ( -1 ) from the square root:

[ f'(x) = \lim_{h \to 0} \frac{\sqrt{2x - 1} - \sqrt{2x - 1 - 2h}}{h\sqrt{2(x + h) - 1}\sqrt{2x - 1}} ]

Now, we can cancel out the ( h ) terms:

[ f'(x) = \lim_{h \to 0} \frac{\sqrt{2x - 1} - \sqrt{2x - 1 - 2h}}{h} \cdot \frac{1}{\sqrt{2(x + h) - 1}\sqrt{2x - 1}} ]

Finally, take the limit as ( h ) approaches 0:

[ f'(x) = \frac{-1}{2(x - 1)^{3/2}} ]

Therefore, the derivative of ( f(x) = \frac{1}{\sqrt{2x - 1}} ) by first principles is ( f'(x) = \frac{-1}{2(x - 1)^{3/2}} ).

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7